Association between advanced NSCLC T790 M EGFR-TKI secondary resistance and prognosis: A observational study. Issue 28 (July 2018) - Wang, Yuli; Wei, Yuan; Ma, Xiaoping; Ma, Xinyu; Gong, Ping
Abstract : Abstract: Epidermal growth factor receptor (EGFR) mutations for EGFR-tyrosine kinase inhibitors (EGFR-TKI) in non-small cell lung cancer (NSCLC) patients are with clinical benefits. Nevertheless, eventual resistance to EGFR-TKI is almost inevitable. In about 50% patients, EGFR-TKI develops a secondary mutation, which is often the T790 M mutation. We aimed to investigate the relationship between EGFR gene status in the peripheral blood and prognosis (progression-free survival [PFS] and overall survival [OS]) in advanced lung adenocarcinoma patients and the 20 exon 790 site mutation (T790 M) and acquired resistance to EGFR-TKI. A total of 49 patients with EGFR-TKI resistance and advanced lung cancer who visited the Shihezi University School of Medicine between 12/2013 and 12/2014 were enrolled in this study. Peripheral blood plasma DNA was isolated after EGFR-TKI resistance and the EGFR exon 20 T790 M mutation was detected using the probe amplification refractory mutation system method. The T790 M mutation rate was 30.6% (15/49). There was no association between T790 M mutation and age, gender, smoking, clinical stage, Eastern Cooperative Oncology Group rating, initial EGFR mutation, and EGFR-TKI drugs, but EGFR-TKI resistance was associated with progression ( P  = .009). Median progression-free survival (PFS) of patients with T790 M mutation was 9.6 months and median overall survival (OS) was 17.6 months, compared to 6.8 and 12.7 months in controls ( P  = .018 and P  = .027). Multivariate analysis showed that T790 M mutations independently affected the PFS (risk ratio, RR = 0.653, 95% confidence interval, CI: 0.069–0.886, P  = .032) and OS (RR = 0.847, 95% CI: 0.208–2.696, P  = .008). T790 M mutation and EGFR-TKI resistance are independent factors to affect PFS and OS of non-small cell lung cancer patients. Abstract : Supplemental Digital Content is available in the text